GEOCHEMICAL FACTOR OF MARSHALLITES LOCALIZATION IN MAGNETITE QUARTZITES CRUST OF WEATHERING IN THE KRYVYI RIH BASIN - Prylepa, D.; Evtekhov, V.; Chasova, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Marshallites are widespread in the iron ore rock mass crust of weathering in the Kryvyi Rih basin: their quantity locally reaches 20% of the total amount of hematite quartzites, which are the product of weathering of primary magnetite quartzites. Extensive researches of marshallites are due to appraisal of supergenically altered ferruginous quartzites as a promising raw material for production of iron ore (hematite) concentrate. Stratigraphic, tectonic and geochemical factors are among the main ones for localizing marshallites. Hematite-containing marshallites were formed by partial dissolution of quartz and by silica removal under the influence of supergene solutions of high alkalinity. Geological observations were conducted by the authors within the Southern iron ore region of the Kryvbas (Skelyuvatske and Valyavkynske deposits), where the largest deposits of hematite quartzites having total reserves of more than 2 billion tons are located. The depth of their distribution reaches 1,000 meters. More than 90% of marshallitized hematite quartzites bodies are located in the upper ferruginous quartzite crust of weathering to a depth of 100 m from the surface of banded iron formation weathering. Meteoric waters acquired increased alkalinity after penetration through calcite and dolomite-bearing sedimentary rocks of the Cenozoic cover, which covers the rock mass of banded iron formation. Studies of pH solutions showed the fact that it ranges from 6-6.5 for rainwater to 9-9.5 on the border of the sedimentary cover and weathered ferruginous quartzites. Below there is a marshallitization zone, in the section of which a decrease in the pH to 7-7.5 at a depth of 70-100 m takes place. Deposition of SiO2 occurs in porous hematite quartzites with the formation of supergene secondary quartzites from saturated silica supergene solutions. The depth of their distribution zone is from 70-100 to 100-150 m, measured from the surface of the weathered iron rock mass. Formation of thin (20-30 m) marshallitization linear zones to a depth of 200 m takes place along the faults, synclinal folds bends and other tectonic disturbances.
Keywords: banded iron formation; Kryvyi Rih basin; crust of weathering; hematite quartzites; marshallites